Valores, juventud y medios de comunicación social - Oyarzún, María Eugenia (Revista Chilena de Humanidades, 2016)
Ms. Oyarzun’s contribution underwrites the great impact of the mediaupon values, in this particular case, of values held by young people in a hightech period. Social communicators, as suggested by the author, have thus a tremendous responsibility in the formation of values as well as their share in the educational process. For these purposes, they should stimulate attitudes of creative response to culture rather than of mere consumerism.